Resenhas - Neuschrank, Aline; do Rosário Toledo, Adilson; Vinícius Liessem Fontana, Marcus; Redmer Hinz, Josiane; Lourenço dos Santos, Rogéria (Revista Linguagem & Ensino, 2019)
Esta seção contém resenhas de cinco livros.